Analisis Kebijakan PERDA Kabupaten Bangkalan Sebagai Kota Dzikir dan Sholawat - Baijuri Alwi; Erna Setijaningrum (Cakrawala Repositori IMWI, 2023)
One of the interesting things in the development of legal products in the regions after the adoption of regional autonomy is the emergence of various regional legal products with sharia nuances. This is also the case in Bangkalan, which in its legal products applies Islamic rules. This study uses normative legal research with a conceptual approach, statute approach, and case approach. The results obtained in this research activity are that the Dzikir and Shalawat activities are expected to be able to resolve the roots of socio-economic problems and the impact can be seen within a certain period of time. Thus it is quite important for Dzikir and Shalawat as a policy not to be confined in the imagination of political discourse and become discourse constructions in the media within the framework of elite populism. so that it does not or has not yet provided a significant impact on the wider community as end users. However, it is important to translate Dhikr and Shalawat as a policy into something more concrete and a public welfare-oriented program.